PENGARUH SUPPLY CHAIN MANAGEMENT PRACTICES DAN MARKETING CAPABILITY TERHADAP FIRM PERFORMANCE MELALUI COMPETITIVE ADVANTAGE - Sri Widyanesti; Siti Masyithah (Universitas Mercu Buana, 2018)
Abstract. Firm performance is something that is produced by a company in a certain period with reference to the standard set. The performance of hotel industry in Bandung tend to be sluggish and decrease performance. This happens because the hospitality business in Bandung City attracted many businessmen supported by an increasing numbers of domestic and foreign tourist visits every year. The purpose of the research is to determine the behavior of supply chain management and marketing ability to the company's performance directly or through the competitive advantage as a mediator This research is multivariate analysis with SEM PLS data processing. The study was conducted on 77 managers hotel taken using stratified random sampling technique. The results show that supply chain management practices have a positive effect on competitive advantage, but do not have influence on the performance. In contrast to marketing capability that has an influence on competitive advantage and firm performance. This study also shows that competitive advantage can mediate the relationship of marketing capability to firm performance, but can not mediate the supply chain management practices relationship to firm performance in the hospitality industry of Bandung City.